A restricted proxy re‐encryption with keyword search for fine‐grained data access control in cloud storage. (9th January 2016) - Chen, Zhenhua; Li, Shundong; Huang, Qiong; Wang, Yilei; Zhou, Sufang
Summary: For fine‐grained data access control in cloud computing, for the first time, we introduce a new concept called restricted proxy re‐encryption with keyword search, which combines the function of proxy re‐encryption with keyword search and that of threshold cryptosystem. To demonstrate this concept, we present the formal syntax for restricted proxy re‐encryption with keyword search, the security model, and a concrete construction. In our scheme, we take advantage of the techniques of threshold cryptosystem to restrict the capacity of the proxy cloud server, and in the meantime, we let the proxy cloud server can only re‐encrypt the data containing a specified keyword, which matches the trapdoor from delegatee to provide an accurate access control for users. While in this process, the proxy cloud server learns nothing about the contents of data and keyword. Our scheme is proved to be semantically secure under the modified bilinear Diffie–Hellman assumption and the q ‐decisional bilinear Diffie–Hellman inversion assumption in the random oracle model. Finally, we apply the techniques in our scheme to some practical problems. Copyright © 2016 John Wiley & Sons, Ltd.